2020
DOI: 10.1002/hon.2714
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of posttransplant lymphoproliferative disorder after allogeneic stem cell transplantation in patients with lymphoma treated with rituximab

Abstract: Posttransplant lymphoproliferative disorder (PTLD) is a serious complication after hematopoietic stem cell transplantation (HSCT). Several studies of risk factors for PTLD have been reported; however, the probability of, and risk factors for, PTLD in patients with lymphoma is unknown. Japanese nationwide transplant registry data from 5270 patients with lymphoma after allogeneic HSCT were analyzed. Mature B‐cell, T/NK‐cell, and T‐cell lymphoblastic subtypes accounted for 49%, 26%, and 9.6% of lymphoma cases, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In CNS-PTLD, it has been reported that time from transplantation to CNS-PTLD can be more than 10 years, and most CNS-PTLDs are associated with latent EBV infection [10]. In the case presented here, in addition to the profound immunosuppression associated with HSCT that triggered the reactivation of EBV infection and ultimately the malignant transformation of B cells, the patient was also subject to other factors, including the transplantation from an HLA-mismatched donor and the use of anti-thymocyte globulin that, based on previous reports, appear to increase the risk of PTLD [10,22].…”
Section: Discussionmentioning
confidence: 68%
“…In CNS-PTLD, it has been reported that time from transplantation to CNS-PTLD can be more than 10 years, and most CNS-PTLDs are associated with latent EBV infection [10]. In the case presented here, in addition to the profound immunosuppression associated with HSCT that triggered the reactivation of EBV infection and ultimately the malignant transformation of B cells, the patient was also subject to other factors, including the transplantation from an HLA-mismatched donor and the use of anti-thymocyte globulin that, based on previous reports, appear to increase the risk of PTLD [10,22].…”
Section: Discussionmentioning
confidence: 68%
“…The preemptive use of rituximab for prevention of PTLD has become a common strategy in EBV viremic hematologic stem-cell transplant (HSCT) [129,130]. B-cell depletion before or directly after HSCT, has shown to reduce EBV replication [131,132] and the incidence of EBV-positive PTLD [133][134][135] in high-risk patients. The potential effect of rituximab on subsequent PTLD development may be attributable to the depletion of CD20 + B-cells, which represent the major reservoir for latent EBV infection.…”
Section: Rituximab For Prevention Of Ebv-positive Ptldmentioning
confidence: 99%